Advances In Bioprinting Of Vascularized Tissue Constructs For Reconstructive Surgery: A Review Of Breakthrough Technologies - Dandoulakis, MD, Emmanouil (Journal of Neonatal Surgery, 2025)
The innovation of 3D bioprinting has brought about a significant change in tissue engineering, particularly in the construction of vascularized tissue structures that play a crucial role in reconstructive surgery. It presents an overview of currently available innovative technologies that permit the development of perfusable vascular networks as an alternative to conventional grafts, which have certain disadvantages related to the supply problem and immunocompatibility concerns. The new resolution levels can be recapitulated using state-of-the-art bioprinting technologies, such as multiscale coaxial printing and two-photon polymerization, to recreate vascular hierarchies. Emerging bioinks, including self-assembling peptides, VEGF bioinks, and magnetically responsive hydrogels, enhance endothelial orientation and mechanical tailorability. This is achieved by providing perfusable channels through microfluidic integration; however, AI-based computational models excel in implementing vascular design and forecasting vascular remodeling. Recent findings include bioprinted constructs capable of anastomosis, which have been successfully integrated into and reconstituted hosts in preclinical studies. Additionally, vascularised organoids have shown improved functionality, with a few notable examples including liver constructs with the integration of bile ducts. Applications include skin, bone, and craniomaxillofacial reconstruction, with clinical translation steps involving first-in-human trials of vascular grafts. Scaffolding issues, such as scalability, cell viability, and regulatory standardization, still exist; however, innovations like in situ bioprinting and 4D shape-morphing constructs are pointing to a revolutionary future. As highlighted by this review, this holds the promise to revolutionize reconstructive surgery, reducing the use of autografts and promising to improve patient outcomes through the personalization and scalability of solutions. Further cross-disciplinary cooperation and funding are needed to overcome the technical and ethical barriers, and avenues should be opened for clinical implementation